The association between the clinical diversity of psoriasis and depressive symptoms: the HUNT Study, Norway. (13th August 2017) - Modalsli, E.H.; Åsvold, B.O.; Snekvik, I.; Romundstad, P.R.; Naldi, L.; Saunes, M.
Abstract: Background: While a number of observational hospital‐based studies have reported an association between psoriasis and depression, less is known about the clinical diversity of psoriasis and depressive symptoms. Objective: To investigate the associations of inverse psoriasis, psoriasis severity and psoriasis duration with depressive symptoms in a general population. Methods: We linked data from the population‐based third Nord‐Trøndelag Health Study (HUNT3) to the Norwegian Prescription Database (NorPD) and Statistics Norway. Depressive symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS). Associations between psoriasis and depressive symptoms (HADS ≥ 8) were estimated using logistic regression. Results: Among 37 833 participants in HUNT3, we found a weak association between any psoriasis and the prevalence of depressive symptoms [fully adjusted odds ratio (OR) 1.12, 95% confidence interval (CI) 0.97–1.28]. The association with depressive symptoms was stronger when psoriasis was characterized by inverse anatomical distribution (OR 1.32, 95% CI 1.02–1.70), requirement of systemic psoriasis medication (OR 1.47, 95% CI 1.00–2.17) or long disease duration (OR 1.33, 95% CI 1.09–1.64). Conversely, when there was no inverse psoriasis distribution, no requirement of systemic medication, or shorter disease duration, psoriasis was not meaningfully associated with depressive symptoms. Conclusion: Overall, depressive symptoms do not seem to be a major concern among subjects with psoriasis in a general Norwegian population. However, among subjects with inverse anatomical distribution, requirement of systemic psoriasis medication or long disease duration, depressive symptoms may be particularly important to address when evaluating the burden of psoriasis.